INVESTASI DAN HAK ASASI MANUSIA: MENCARI TITIK TEMU ANTARA PERATURAN PRESIDEN NO. 60 TAHUN 2023 TENTANG BISNIS DAN HAK ASASI MANUSIA DAN PROGRAM BUSINESS READY - Muhammad, Fahrurozi (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2024)
Indonesia has enacted Presidential Regulation No. 60 of 2023 on Business and Human Rights National Strategy. This regulation is intended to enhance efforts of human rights protection in business practices inspired by United Nations Guiding Principles on Business and Human Rights. In the same year, the World Bank also introduced Business Ready, which serves as Indonesia’s primary policy for investment. Through the utilization of the normative juridical method and secondary data analysis, this study examines the substance of the Presidential regulation and the World Bank's initiative. This research is aimed to find the intersection between Indonesia's concern for protecting human rights and boosting the economy through its Presidential Regulation and its national investment policy. It finds that the Regulation lacks of mandate for human rights due diligence. Additionally, it notes that the B-Ready initiative primarily emphasizes economic, labor, and consumer protection rights, without comprehensively addressing broader human rights enforcement.